Financial Performance and Corporate Social Responsibility on Firm Value - Kusvilanda, Maera Mauhibah; Sukiswo, Helmy Wahyu (Universitas Gorontalo, 2026)
This study aims to analyze the effect of financial performance, as measured by Return on Equity (ROE), and Corporate Social Responsibility (CSR) on firm value in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The data were analyzed using multiple linear regression with the assistance of SPSS version 26. The sampling method employed was purposive sampling, resulting in a sample of 15 banking companies. The results indicate that financial performance has a significant effect on firm value. Furthermore, Corporate Social Responsibility also has a significant effect on firm value. These findings suggest that strong financial performance and effective implementation of corporate social responsibility play an important role in shaping positive investor perceptions of banking companies. Therefore, both factors contribute to corporate sustainability, enhance managerial efficiency, and strengthen competitiveness in the financial services sector.